Defective Fe3O4‐x Few‐Atom Clusters Anchored on Nitrogen‐Doped Carbon as Efficient Oxygen Reduction Electrocatalysts for High‐Performance Zinc–Air Batteries. Issue 7 (3rd June 2022) - Chu, Panpan; Zhang, Yingmeng; He, Jiajie; Chen, Jinhong; Zhuang, Jingjun; Li, Yongliang; Ren, Xiangzhong; Zhang, Peixin; Sun, Lingna; Yu, Bingzhe; Chen, Shaowei
Abstract: It remains a challenge to develop cost‐effective, high‐performance oxygen electrocatalysts for rechargeable metal–air batteries. Herein, zinc‐mediated zeolitic imidazolate frameworks are exploited as the template and nitrogen and carbon sources, onto which is deposited a Fe3 O4 layer by plasma‐enhanced atomic layer deposition. Controlled pyrolysis at 1000 °C leads to the formation of high density of Fe3 O4‐ x few‐atom clusters with abundant oxygen vacancies deposited on an N‐doped graphitic carbon framework. The resulting nanocomposite (Fe3 O4‐ x /NC‐1000) exhibits a markedly enhanced electrocatalytic performance toward oxygen reduction reaction in alkaline media, with a remarkable half‐wave potential of +0.930 V versus reversible hydrogen electrode, long‐term stability, and strong tolerance against methanol poisoning, in comparison to samples prepared at other temperatures and even commercial Pt/C. Notably, with Fe3 O4‐ x /NC‐1000 as the cathode catalyst, a zinc–air battery delivers a high power density of 158 mW cm −2 and excellent durability at 5 mA cm −2 with stable 2000 charge–discharge cycles over 600 h. This is ascribed to the ready accessibility of the Fe3 O4‐ x catalytic active sites, and enhanced electrical conductivity, oxygen adsorption, and electron‐transfer kinetics by surface oxygen vacancies. Further contributions may arise from the highly conductive and stable N‐doped graphitic carbon frameworks. Abstract : Plasma‐enhanced atomic layer deposition is employed to deposit a layer of Fe3 O4 onto a zeolite imidazole framework precursor. Pyrolysis leads to the production of a nitrogen‐doped carbon scaffold embedded with defective Fe3 O4‐ x few‐atom clusters. The sample with the highest concentration of oxygen vacancies exhibits the best oxygen reduction reaction activity and optimal performance as the air‐cathode catalyst for zinc–air battery.